2006
DOI: 10.1016/j.nuclphysb.2006.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehogs in Wilson loops and phase transition in SU(2) Yang–Mills theory

Abstract: We suggest that the gauge-invariant hedgehoglike structures in the Wilson loops are physically interesting degrees of freedom in the Yang-Mills theory. The trajectories of these "hedgehog loops" are closed curves corresponding to center-valued (untraced) Wilson loops and are characterized by the center charge and winding number. We show numerically in the SU(2) Yang-Mills theory that the density of hedgehog structures in the thermal Wilson-Polyakov line is very sensitive to the finite-temperature phase transit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Using the results of Refs. [12,13] obtained for the SU (2) Yang-Mills theory of the gauge-invariant hedgehog-like structures in the Wilson loops, we have considered the lattice theory giving the critical value of temperature for the hedgehogs confinement phase. Considering the hedgehog lattice theory, we have concluded that hedgehogs can exist only at the energy scale µ 10 4 GeV.…”
Section: Introductionmentioning
confidence: 99%
“…Using the results of Refs. [12,13] obtained for the SU (2) Yang-Mills theory of the gauge-invariant hedgehog-like structures in the Wilson loops, we have considered the lattice theory giving the critical value of temperature for the hedgehogs confinement phase. Considering the hedgehog lattice theory, we have concluded that hedgehogs can exist only at the energy scale µ 10 4 GeV.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of Ref. [13] investigated the gauge-invariant hedgehog-like structures in the Wilson loops of the SU(2) Yang-Mills theory. In this model the triplet Higgs fieldΦ = 1 2 Φ a σ a vanishes at the centre of the monopole x = x 0 : Φ(x 0 ) = 0, and has a generic hedgehog structure in the spatial vicinity of this monopole.…”
Section: Hedgehogs In the Wilson Loops And The Phase Transition In Thmentioning
confidence: 99%
“…In Section 8 hedgehogs in Wilson loops of the SU(2) Yang-Mills theory, and phase transitions in this theory were investigated using the results of Refs. [13,14]. Their lattice results gave the critical value of the temperature for the hedgehog's confinement phase: β crit ≈ 2.5, and this result gives the value of critical temperature T c ∼ 10 18 GeV.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Ref. [20] the gauge-invariant hedgehog-like structures in the Wilson loops were investigated in the SU (2) Yang-Mills theory. In this model the triplet Higgs field Φ ≡ 1 2 Φ a σ a (a = 1, 2, 3) vanishes at the center of the monopole x = x 0 : Φ(x 0 ) = 0 (33) and has a generic hedgehog structure in the spatial vicinity of this monopole.…”
Section: What Is the Universe Vacuum?mentioning
confidence: 99%